Thermo-Responsive Complexes of c-Myc Antisense Oligonucleotide with Block Copolymer of Poly(OEGMA) and Quaternized Poly(4-Vinylpyridine) - Topuzogullari, Murat; Elalmis, Yeliz Basaran; Isoglu, Sevil Dincer (WILEY-V C H VERLAG GMBH, 2017)
Solution behavior of thermo-responsive polymers and their complexes with biological macromolecules may be affected by environmental conditions, such as the concentration of macromolecular components, pH, ion concentration, etc. Therefore, a thermo-responsive polymer and its complexes should be characterized in detail to observe their responses against possible environments under physiological conditions before biological applications. To briefly indicate this important issue, thermo-responsive block copolymer of quaternized poly(4-vinylpyridine) and poly(oligoethyleneglycol methyl ether methacrylate) as a potential nonviral vector has been synthesized. Polyelectrolyte complexes of this copolymer with the antisense oligonucleotide of c-Myc oncogene are also thermo-responsive but, have lower LCST (lower critical solution temperature) values compared to individual copolymer. LCST values of complexes decrease with molar ratio of macromolecular components and presence of salt. Dilution of solutions also affects solution behavior of complexes and causes a significant decrease in size and an increase in LCST, which indicates possible effects of severe dilutions in the blood stream.
Keywords: nonviral vector; polyelectrolyte complex; temperature-responsive polymer; OLIGO(ETHYLENE GLYCOL) METHACRYLATE; GENE DELIVERY; NANOPARTICLE DELIVERY; RESPONSIVE POLYMERS; IN-VIVO; DNA; MICELLES; CELLS; POLY(N-ISOPROPYLACRYLAMIDE); POLYMERIZATION; Biochemistry & Molecular Biology; Materials Science; Polymer Science